A Survey on Factors Promoting Early and Delayed Complications in Neonate and Infants Using Cvc Line: A survey on factors complications in neonate and infants using CVC line - peyvasteh, mehran; Shafieyan, Tuba; Askarpur, shahnam; Motamedfar, Azim; Shafieyan, Tuba; kazemnia, khalil (Iranian Journal of Pediatric Surgery, 2023)
Abstract Introduction: Central venous catheter placement (CVC) is an accepted venous access method in the treatment of critically ill neonates & infants, evaluation of factors that induce complications are nescessary. Therefore, the aim of this study was to investigate the effective factors in causing early and late complications of central venous catheter placement in infants less than one year hospitalized in Imam Khomeini and Golestan hospitals. Methods: This study was performed on 400 infants less than one year old. Patients informations,early and delayed complications were recorded. Data were compared based on Chi-square and Fisher tests. Results: The most common complication of central venous catheter placement in the neonates and infants were as followed, infection (5.5%), venous thrombosis (5%), thrombophlebitis (4.3%), bleeding (3.8 %), hematoma (2.5%), arterial injury (0.3%) and pneumothorax (0.3%). Hemothorax and malposition were not observed. Frequency of bleeding in patients in whom catheterization was attempted 3 times was significantly higher (75%) than patients that had been tried twice (26.3%). Also, the frequency of hematoma and arterial injury were higher in cases who had tried twice. Finally, one case of pneumothorax was observed in cases who had been tried three times (25%). Also, the incidence of infection and thrombophlebitis in patients who had a catheter for more than 14 days was significantly higher than patients who had a catheter less than 14 days. However, it was found that the frequency of complications was not related to age, sex, height and weight, underlying disease of the infant, catheter location and catheter needle. Conclusion: The incidence of central venous catheter complications in infants is low and has a significant relationship with the attempting times of placement and duration of catheter placement. This is a suitable venous access method for the treatment of infants and had no association with the underlying disease and neonatal demographic indicators. Keywords: Central venous catheter, Early and late complications, Infant Abstractter, Early and late complications, Infant